Prestress losses in reinforced concrete beams strengthened with NSM-CFRP laminates - Costa, Inês G. (2015)
Using prestressed near surface mounted fibre reinforced polymers (NSM-FRP) is nowadays regaining the attention from the scientific community for the strengthening of existing reinforced concrete (RC) structures. The application of prestressed internal FRP bars and externally bonded prestressed FRPs has already been deeply investigated and revealed considerable benefits when compared to the corresponding passive solutions. A certain amount of prestress provides benefits mainly associated to structural integrity and material durability. Immediately after prestress transference, it is possible to close some of the existing cracks, decreasing the susceptibility of the element to corrosion and, a certain amount of deflection can be recovered due to the creation of a negative curvature. However, very few studies have been carried out to properly assess the preservation of prestress over time. In this context, several reinforced concrete beams strengthened with prestressed NSM carbon FRP (CFRP) laminates were prestressed and monitored for about 40 days. The data obtained from these experimental programs is in this paper presented and analysed. The observed prestress losses were later modelled using finite elements analysis and, although this topic is not addressed in this paper, the obtained results revealed considerable precision. The largest strain losses in the CFRP laminate were found to be mainly located in the extremities of the bonded length, while in the central zone most of the applied pre-strain was retained over time. The highest CFRP strain losses were observed in the first 6 to 12 days after prestress transfer, suggesting that the application of prestressed NSM-FRP will be very effective over time.